2001
DOI: 10.1093/clinchem/47.7.1212
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Hemoglobin A1c (HbA1c) Values among Diabetic Patients

Abstract: Background: Few studies have examined patients’ views, knowledge, and understanding of glycohemoglobin A1c (HbA1c) testing. We explored such issues in patients with type 1 diabetes and used their statements to estimate analytical quality specifications for HbA1c testing. Methods: We recruited 201 patients from a hospital outpatient clinic. A questionnaire was used to collect information on diabetes characteristics, perceived knowledge of HbA1c, last HbA1c value, HbA1c target value, and threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…36 The inverse correlation between duration of diabetes and HbA 1c levels in our study is also in agreement with the results of other investigators. 37 HbA 1c levels are reduced with time as diabetic patients gain knowledge and personal experience in managing the disease. A significant positive correlation was detected between duration of diabetes and the KA score, which is particularly inter esting because no such correlation was found between age and the KA score or between age and HbA 1c levels.…”
Section: Methodsmentioning
confidence: 99%
“…36 The inverse correlation between duration of diabetes and HbA 1c levels in our study is also in agreement with the results of other investigators. 37 HbA 1c levels are reduced with time as diabetic patients gain knowledge and personal experience in managing the disease. A significant positive correlation was detected between duration of diabetes and the KA score, which is particularly inter esting because no such correlation was found between age and the KA score or between age and HbA 1c levels.…”
Section: Methodsmentioning
confidence: 99%
“…HbA1c can be defined as an objective measure for lifestyle behaviour change. Regular monitoring of HbA1c values which is measured in clinical settings is now the principal way to measure and track longterm glycaemic control objectively in diabetes 42 . Knowledge, attitude and motivation are the most important for the patients' ability to make behavioural changes to maintain or reduce HbA1c levels 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring of HbA1c values which is measured in clinical settings is now the principal way to measure and track longterm glycaemic control objectively in diabetes 42 . Knowledge, attitude and motivation are the most important for the patients' ability to make behavioural changes to maintain or reduce HbA1c levels 42 . In the present study, the HC groups compared with the HE groups significantly enhanced their lifestyles in line with the significantly higher improvement in HbA1c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harwell et al [87] conducted a telephone survey in a rural population group and found that the participants knew their last A1C value, but they could not interpret the value properly. Skeie et al [88] found that the highknowledge group, that included individuals who had diabetes for a longer time period, had a better understanding of A1C compared to the low-knowledge group. Evidence shows that as an individual's knowledge of diabetes management increases the A1C values decrease.…”
Section: Role Of Diabetes Educatorsmentioning
confidence: 99%